Cannibalism in Holocene muricid snails in the Beagle Channel, at the extreme southern tip of South America: an opportunistic response? - Gordillo, Sandra (2013)
This work documents the occurrence of drillholes on muricid Trophon geversianus shells from a Holocene raised marine deposit in the Beagle Channel, located on the extreme southern tip of South America (~ 55ºS). Based on drillhole morphology and previous data under laboratory conditions these predatory holes are attributed to conspecifics, thus suggesting cannibalism. It appears that when food is scarce and the alternative prey (Tawera gayi and other clams) is not available, T. geversianus may increase the frequency of cannibalism in order to compensate for the loss of bivalve prey. Cannibalism therefore developed at ca. 4000 yr. BP as a response to the lack of clams, which would have disappeared during a sudden hydrological local event that affected the filter feeders.